Effects of mistletoe products on pharmacokinetic drug turnover by inhibition and induction of cytochrome P450 activities - Michael Schink; Oliver Dehus (BMC, 2017)
Abstract Background European mistletoe (Viscum album) products used in cancer therapy are frequently combined with other anti-cancer-drugs. Hence, potential herb-drug interactions have become a major safety concern in mistletoe therapy. Methods Three European mistletoe products (Helixor® A, Helixor® M and Helixor® P from mistletoe grown on firs, apple trees and pines, respectively) were tested for inhibition of nine major cytochrome P450 (CYP) isoenzymes in a test system using pooled human liver microsomes and for induction of five CYP isoforms in human hepatocytes cultivated in vitro according to the relevant guideline. Results Major inhibition did not occur in any of the CYP marker reactions. For some CYP isoenzymes, a minor or intermediate inhibition could be observed, but without dose effect relationship. Induction activity (≥ 1.5-fold increase) was not found with any of the three mistletoe products. Conclusion Since no induction capacity was found and major inhibition above 50% did not occur even with the highest concentration used, which is approximately 100,000-fold higher than the clinically relevant dose in plasma, a clinically relevant herb-drug interaction is not expected for Helixor® A, M, and P.